Estimating the spawning activity of fish species using nuclear and mitochondrial environmental DNA concentrations and their ratios. (9th November 2022) - Wu, Luhan; Wu, Qianqian; Inagawa, Takashi; Okitsu, Jiro; Sakamoto, Shogo; Minamoto, Toshifumi
Abstract: During spawning activity, fish release large amounts of sperm and eggs into the water, which has been assumed to cause an increase in environmental DNA (eDNA) levels and nuclear DNA/mitochondrial DNA ratios. To test whether these assumptions are valid and whether nuclear and mitochondrial eDNA analysis can be used to monitor the spawning activity of freshwater fish, we conducted field eDNA surveys and traditional surveys using common carp ( Cyprinus carpio ), largemouth bass ( Micropterus salmoides ) and bluegill sunfish ( Lepomis macrochirus ) as model species. Fish spawning periods were estimated based on age, as estimated using the body lengths of juveniles collected in the Miharu reservoir in Fukushima, Japan. The results showed that the main spawning periods of largemouth bass and bluegill sunfish were from April to July and from July to August, respectively. Field eDNA surveys were conducted in the Hebisawagawa front reservoir, which is connected to the Miharu reservoir. From March to August 2019 and 2020, weekly eDNA sampling was conducted at three sites, and daily sampling was conducted at six sites from 23 June to 3 July 2020. The eDNA concentrations of the nuclear internal transcribed spacer 1 (ITS1) and mitochondrial cytochrome B (CytB), as well as the ITS1/CytB ratio, were measured for each of the three fish in each water sample. Water temperature had a statistically significant effect on eDNA concentration, probably reflecting the relationship between water temperature and spawning. We created generalised additive mixed models to estimate spawning activity periods based on weekly eDNA data. The estimated periods of spawning activity for common carp, largemouth bass and bluegill sunfish were March to May, May to July, and May to August, respectively. The estimated spawning periods coincided with known fish ecology or the results of traditional methods. This method also has been applied to daily eDNA samples, showing the feasibility of high‐resolution estimation of spawning activity. For common carp and bluegill sunfish, we were able to estimate the spawning period using this method. Although the method is affected by biomass and the diffusion and degradation of eDNA, it has the potential to accurately estimating spawning activities. These then can be estimated without conducting laborious traditional surveys, facilitating the monitoring of reproduction by rare, invasive or important fishery species. Further research on the diffusion distance and degradation time of the eDNA concentration peak caused by fish spawning activity may improve the accuracy of monitoring.